Financial Literacy and Financial Welfare: The Mediating Role of Financial Planning and the Moderating Effect of Lifestyle in Bekasi - Aisaturahma Aisaturahma; Bunga Puja Ananda; Iis Fauziah; Friska Fariska; Stifani Rahardjo (DEAL: International Journal of Economics and Business, 2025)
Financial well-being can be achieved when individuals have sufficient knowledge, are able to make financial plans and have a lifestyle that is in accordance with their financial capabilities. Therefore, the purpose of this study is to examine the effect of financial literacy on financial well-being through financial planning, as well as observe how lifestyle acts as a moderating factor for those at productive age in Bekasi. The method used is a quantitative-based approach using PLS-SEM, which involves collecting data through distributing questionnaires. The results show that the direct influence of financial literacy and financial planning is able to contribute to financial well-being, but lifestyle does not contribute to financial well-being. In addition, the indirect effect, namely the financial planning variable acting as a mediation path, is able to mediate the relationship with financial well-being, while the indirect effect, namely the lifestyle variable as moderation, is not proven to strengthen or weaken the relationship with financial well-being. This finding provides a theoretical contribution by highlighting that lifestyle, which is often assumed to be a significant determinant of financial well-being, does not always play a moderating role. Such results suggest that in the context of productive-age individuals with limited income in Bekasi, financial literacy and planning have stronger explanatory power than lifestyle. The novelty of this study lies in revealing that lifestyle differences may not reduce or amplify the impact of financial literacy on financial well-being, offering new insights for financial behavior literature in emerging markets.